“We Are Living in Survival Mode”: Lived Experiences of Syrian Refugees and Forcibly Displaced Ukrainians in Northern Ontario - Thakur, Monika (Refuge, 2025)
This article provides an understanding of the lived experiences of Syrian refugees and forcibly displaced Ukrainians living in Sault Ste. Marie, a small city in northern Ontario, using personal narratives. The comparative analysis reveals diverse but overlapping integration challenges, with the aim to expand academic and policy knowledge about refugee integration in small cities in northern Ontario. Findings highlight that both groups faced similar challenges including limited employment, discrimination, language barriers, and inadequate health care. Despite these obstacles, participants valued affordable housing, access to nature, and a welcoming community. Limited job opportunities remained a major barrier to retention.